Le latin dans le système éducatif allemand de la première moitié du xixe siècle - Christophe Bertiau (Recherches Germaniques)
In a recent book, the historian Bas van Bommel has convincingly challenged the validity of the concept of “neo–humanism” (Neuhumanismus) as a description for nineteenth-century humanism in Germany. Bas van Bommel argues that, far from having put any “neo–humanist” project into practice, the contemporaneous German educational system mainly preserved the tradition of the previous centuries. However, in undertaking this historical revision, I claim, the author has also understated some of the changes that were underway in the German educational system in the mentioned period. My research therefore disputes Bas van Bommel’s criticism, while at the same time deploying it to determine how great the importance of Latin really was in the German educational system in the first half of the 19th century. The instruction of Latin, I assert, was not neglected because of a “neo–humanist” predilection for ancient Greek ; rather, it continued to dominate the “secondary” education (höheres Schulwesen) and still maintained a respectable status at university, although having clearly lost some of its previous prerogatives. Only late in the 19th century did some changes dating back to the period around 1800 undermine the supremacy of Latin education in Germany.